ON THE DESIGN OF COATING SYSTEM USING NANOMECHANICAL EXPERIMENTS - David Mercier; Claes Fredriksson (Acta Polytechnica CTU Proceedings)
The aim of this paper is to identify performance indices for the design of coating systems, using results from nanomechanical tests. The use of nanoindentation, nanoscratch and pin-on-disk experiments applied to coatings for mechanical and tribological property estimation is presented. Then, multiple performance indices, based on experimental and numerical results found in the litterature, are listed in order to help the material selection and optimization of durability and performance of coatings.